The Performance of CIP Scheme in Solving Advection Equation - Fei, Tan Jeff; Tion, Puay How (International Journal on Engineering Technology and Infrastructure Development, 2024)
Constrained interpolation profile (CIP) approach is reviewed in this paper. This research provides a performance comparison between CIP and upwind scheme, a different general method for solving advection equations. The performance of numerical method will be judged based on its accuracy in solving advection equation. The simulation results indicate that CIP scheme advection is more accurate than Upwind scheme advection due to its minor numerical deviation from exact solution.